2019
DOI: 10.3390/ijerph16091634
|View full text |Cite
|
Sign up to set email alerts
|

Conditions Leading to Elevated PM2.5 at Near-Road Monitoring Sites: Case Studies in Denver and Indianapolis

Abstract: We examined two near-road monitoring sites where the daily PM2.5 readings were among the highest of any near-road monitoring location in the U.S. during 2014–2016: Denver, Colorado, in February 2014 and Indianapolis, Indiana, in November 2016. At the Denver site, which had the highest measured U.S. near-road 24-hr PM2.5 concentrations in 2014, concentrations exceeded the daily National Ambient Air Quality Standards (NAAQS) on three days during one week in 2014; the Indianapolis site had the second-highest numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 46 publications
(61 reference statements)
3
8
0
Order By: Relevance
“…According to Kinney et al, (2011), daytime concentrations of PM 2.5 at the sites adjacent to roadways ranged from 50.7-128.7 µg m -3 which were higher than WHO's 24-hour average guideline (25 µg m -3 ) (WHO, 2005). A similar study conducted by Brown et al, (2019) also reported elevated PM 2.5 concentrations at the near-road sampling sites in Denver and Indianapolis. It is indicative that traffic emissions contribute to PM 2.5 levels in the environment and may also cause health damage to people exposed to it.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…According to Kinney et al, (2011), daytime concentrations of PM 2.5 at the sites adjacent to roadways ranged from 50.7-128.7 µg m -3 which were higher than WHO's 24-hour average guideline (25 µg m -3 ) (WHO, 2005). A similar study conducted by Brown et al, (2019) also reported elevated PM 2.5 concentrations at the near-road sampling sites in Denver and Indianapolis. It is indicative that traffic emissions contribute to PM 2.5 levels in the environment and may also cause health damage to people exposed to it.…”
Section: Introductionsupporting
confidence: 62%
“…PM 2.5 has also been identified as one of the major contributor in traffic-related air pollution (TRAP) (Chao et al, 2018;Xiang et al, 2019;Min et al, 2020). Motor vehicle traffic is an important source of harmful emissions of PM 2.5 in the cities of developing countries (Kinney et al, 2011;Brown et al, 2019). According to Kinney et al, (2011), daytime concentrations of PM 2.5 at the sites adjacent to roadways ranged from 50.7-128.7 µg m -3 which were higher than WHO's 24-hour average guideline (25 µg m -3 ) (WHO, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Spatial obstructions like buildings and trees affect the dispersion and concentration of PM2.5 [3,[9][10][11]. Land use regression models incorporating the buildings' morphological characteristics to estimate PM2.5 and PM10 during stable meteorological conditions improved the model's R 2 by 10% in the high-density area of downtown Hong Kong [3].…”
Section: Introductionmentioning
confidence: 99%
“…Seagram et al 17 updated the DeWinter et al 16 analysis through 2016 and reported a PM 2.5 concentration increment at near-road sites ranging from 0.6 to 1.1 μg m −3 (6−10%). Brown et al 18 found that two sites (in Denver, CO and Indianapolis, IN) from the Near-Road Network had elevated PM 2.5 concentrations that peaked when the sites were near-downwind (15°to 45°) rather than directly downwind (within 15°) from the highway. More recently, several studies have utilized the Near-Road Network sites to determine pollutant increments as a function of time of day, 19 PM 2.5 measurement technique (among other parameters), 20 and land use (among other parameters).…”
Section: ■ Introductionmentioning
confidence: 99%
“…The upwind hourly increment, on the other hand, peaks at 1.1 ± 0.5 μg m −3 and is <0.5 μg m −3 for most hours of the day. This elevated PM 2.5 hourly increment downwind of the highway is consistent with the results from Brown et al, 18 which found that the increment was highest at the and Indianapolis near-road sites when the site was 30°offset from being directly downwind of the highway.…”
Section: ■ Introductionmentioning
confidence: 99%